The Interplay of Stress and Sleep Impacts BDNF Level - Giese, Maria; Unternaehrer, Eva; Brand, Serge; Calabrese, Pasquale; Holsboer-Trachsler, Edith; Eckert, Anne (PLOS ONE, 2013)
Background Sleep plays a pivotal role in normal biological functions. Sleep loss results in higher stress vulnerability and is often found in mental disorders. There is evidence that brain-derived neurotrophic factor (BDNF) could be a central player in this relationship. Recently, we could demonstrate that subjects suffering from current symptoms of insomnia exhibited significantly decreased serum BDNF levels compared with sleep-healthy controls. In accordance with the paradigm indicating a link between sleep and BDNF, we aimed to investigate if the stress system influences the association between sleep and BDNF. Methodology/Principal Findings Participants with current symptoms of insomnia plus a former diagnosis of Restless Legs Syndrome (RLS) and/or Periodic Limb Movement (PLM) and sleep healthy controls were included in the study. They completed questionnaires on sleep (ISI, Insomnia Severity Index) and stress (PSS, Perceived Stress Scale) and provided a blood sample for determination of serum BDNF. We found a significant interaction between stress and insomnia with an impact on serum BDNF levels. Moreover, insomnia severity groups and score on the PSS each revealed a significant main effect on serum BDNF levels. Insomnia severity was associated with increased stress experience affecting serum BDNF levels. Of note, the association between stress and BDNF was only observed in subjects without insomnia. Using a mediation model, sleep was revealed as a mediator of the association between stress experience and serum BDNF levels. Conclusions This is the first study to show that the interplay between stress and sleep impacts BDNF levels, suggesting an important role of this relationship in the pathogenesis of stress-associated mental disorders. Hence, we suggest sleep as a key mediator at the connection between stress and BDNF. Whether sleep is maintained or disturbed might explain why some individuals are able to handle a certain stress load while others develop a mental disorder.